2016
DOI: 10.1126/science.aaf9030
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivation and inactivation of Arabidopsis cryptochrome 2

Abstract: Cryptochromes are blue-light receptors that regulate development and the circadian clock in plants and animals. We found that Arabidopsis cryptochrome 2 (CRY2) undergoes blue light–dependent homodimerization to become physiologically active. We identified BIC1 (blue-light inhibitor of cryptochromes 1) as an inhibitor of plant cryptochromes that binds to CRY2 to suppress the blue light–dependent dimerization, photobody formation, phosphorylation, degradation, and physiological activities of CRY2. We hypothesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
222
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 169 publications
(246 citation statements)
references
References 39 publications
20
222
0
4
Order By: Relevance
“…Homodimerization is required for the phosphorylation and physiological activity of the crys [50][51][52]. Recently, it was found that cry2 forms a homodimer in response to B light [53]. Thus, these results indicate that B light-dependent homodimerization is the elementary process of cry2 photoactivation.…”
Section: Physiological Functions and Actions Of Cryptochromementioning
confidence: 70%
See 2 more Smart Citations
“…Homodimerization is required for the phosphorylation and physiological activity of the crys [50][51][52]. Recently, it was found that cry2 forms a homodimer in response to B light [53]. Thus, these results indicate that B light-dependent homodimerization is the elementary process of cry2 photoactivation.…”
Section: Physiological Functions and Actions Of Cryptochromementioning
confidence: 70%
“…The B light inhibitors of cryptochromes (BIC) 1 and 2 were identified as negative regulators of cry1 and cry2, and they interact with cry2 to suppress the B light-dependent dimerization, phosphorylation, and physiological activities. Therefore, BIC1 and BIC2 constitute the desensitizing mechanism of both crys to sustain the homeostasis of physiologically active cry [53]. However, whether BICs inhibit cry1 dimer formation remains to be tested.…”
Section: Physiological Functions and Actions Of Cryptochromementioning
confidence: 99%
See 1 more Smart Citation
“…These results demonstrate that homodimerization or oligomerization is necessary for the function of plant cryptochromes. Although no obvious blue light dependence was detected for the CRY1 or CRY2 dimerization in those earlier experiments [32 •• ], the blue light-dependent homodimerization, also referred to as photodimerization, of Arabidopsis CRY1 and CRY2 has been recently detected in human HEK293 cells and in transgenic plants expressing near stoichiometric amounts of two recombinant CRY proteins fused to different epitope tags [36 •• ,37] (Q. Wang, unpublished results). Cryptochrome photodimerization is apparently a regulated process in plant cells.…”
Section: Cry Photodimerizationmentioning
confidence: 97%
“…Cryptochrome photodimerization is apparently a regulated process in plant cells. Two closely related CRY inhibitory proteins, referred to as BIC1 and BIC2 (Blue-light Inhibitor of Cryptochromes 1 and 2), were identified in a genetic screen to search for negative regulators of cryptochromes [36 •• ]. BICs inhibit blue light-dependent CRY2 homo-dimerization, oligomerization, and photobody formation.…”
Section: Cry Photodimerizationmentioning
confidence: 99%